1987
DOI: 10.1007/bf00584766
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular sodium on heart muscle energetics

Abstract: A study has been made of changing external sodium concentration [Na]e, over the range 75 to 200 mmol X l-1, on contractile parameters and heat production in isolated, arterially perfused, interventricular rabbit septa.- The observed changes in maximum rate of contraction with [Na]e, either in the presence of a constant external Ca concentration [Ca]e or in the presence of a constant [Na]e2/[Ca]e ratio, paralleled those observed for tension development (T). On the other hand the maximal rate of relaxation (-Tma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Although it is purely speculative, it can be hypothesized that whereas lithium might be inhibiting the forward and reverse mode of the NCX, on the outside of the cell it will be competing with 145 meq Na ϩ /l and on the inside of the cell with perhaps Յ5 meq Na ϩ /l. This agrees with the previous finding that reduction of extracellular Na ϩ (which should particularly influence the NCX) increases the ratio of ϪdT/dt to T (i.e., the speed of relaxation normalized to the maximum tension developed during a contraction) (45).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although it is purely speculative, it can be hypothesized that whereas lithium might be inhibiting the forward and reverse mode of the NCX, on the outside of the cell it will be competing with 145 meq Na ϩ /l and on the inside of the cell with perhaps Յ5 meq Na ϩ /l. This agrees with the previous finding that reduction of extracellular Na ϩ (which should particularly influence the NCX) increases the ratio of ϪdT/dt to T (i.e., the speed of relaxation normalized to the maximum tension developed during a contraction) (45).…”
Section: Discussionsupporting
confidence: 88%
“…The trans-SL inward movement of Ca 2ϩ during the action potential seems to be mediated by voltage-operated channels (23,37,45) and by the NCX (25,52). Depending on the Na ϩ and Ca 2ϩ electrochemical gradients, the NCX can operate in a Ca 2ϩ -influx mode (8,9,28).…”
Section: Discussionmentioning
confidence: 99%
“…The calorimetric approach was widely used to estimate changes in exothermic cellular processes during cardiac activity and resting state by the thermopiles method (Loiselle 1987). In particular, online calorimetry for perfused tissues was extensively employed for studying the energetics of Ca 2+ movement in the steady beating heart (Ponce-Hornos et al 1982;Ponce-Hornos et al 1987;Ponce-Hornos et al 1992), under the transient conditions of a beat (Ponce-Hornos et al 1995;Consolini et al 1997;Ma ´rquez et al 1997;Bonazzola et al 2002), and also during isolated beats under ischemia and hypoperfusion (Consolini et al 2001). With this methodology, the role of mNCX and the effects of clonazepam on the postischemic recovery of a beating heart exposed or not to a high-K + cardioplegia were evaluated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Energy expenditure by the quiescent myocardium includes the operation of active transport systems associated with the sarcolemma (SL), sarcoplasmic reticulum (SR) and mitochondria (MIT) which maintain ionic cell homeostasis. It has been shown that cardiac resting metabolism is affected by changes in extracellular ionic composition which alter the behaviour of the associated ionic transport systems (Ponce‐Hornos et al. 1987, 1992, Cooper et al.…”
mentioning
confidence: 99%
“…Keywords basal metabolism, calcium depletion, calorimetry, mitochondrial Ca 2+ cycling.Energy expenditure by the quiescent myocardium includes the operation of active transport systems associated with the sarcolemma (SL), sarcoplasmic reticulum (SR) and mitochondria (MIT) which maintain ionic cell homeostasis. It has been shown that cardiac resting metabolism is affected by changes in extracellular ionic composition which alter the behaviour of the associated ionic transport systems (Ponce-Hornos et al 1987, Cooper et al 2001. Although changes in extracellular calcium concentration (Ca 2+ o ) in the submillimolar to millimolar range do not modify the energetic cost associated with cardiac…”
mentioning
confidence: 99%